Teacher-Reported Deep Learning Implementation and Students’ Learning Interest in Elementary Schools of Sekayam Subdistrict - Fikry Kusyadi; Vikram Yuda Octa Firandhi (Jurnal Ilmiah Guru Madrasah, 2026)
Students’ learning interest is an important dimension of elementary education because it is closely related to engagement, participation, and students’ willingness to sustain learning activities. In the context of Kurikulum Merdeka, the deep learning approach has been increasingly discussed as a pedagogical strategy that may support meaningful, mindful, and joyful learning. This study aimed to examine the exploratory association between teacher-reported deep learning implementation and fourth-grade students’ learning interest in elementary schools of Sekayam Subdistrict. A small-scale exploratory quantitative survey design was employed. The study involved 85 fourth-grade students from four elementary schools and four homeroom teachers representing different school contexts, including remote, mixed rural-urban, and subdistrict-center settings. Data were collected using two closed-ended questionnaires: a 12-item learning interest questionnaire completed by students and a 12-item deep learning implementation questionnaire completed by teachers. The data were analyzed using descriptive statistics, validity and reliability tests, residual normality testing, homogeneity testing, and exploratory simple linear regression. The learning interest questionnaire was valid and reliable, with item-total correlations ranging from 0.477 to 0.663 and a Cronbach’s alpha value of 0.784. The regression result showed a positive coefficient for deep learning implementation, but the association was not statistically significant (B = 0.463; Beta = 0.177; p = 0.106). These findings suggest a weak positive tendency between teacher-reported deep learning implementation and students’ learning interest; however, the available data did not provide sufficient statistical evidence to confirm a significant relationship.